Evaluación del extracto acuoso a base de semillas de Higuerilla (Ricinus Communis l.) como método de control de nematodos en tomate (Solanum lycopersicum l.) bajo condiciones semi hidropónicas. - Saravia Oña, Josselyn Carolina (2021)
Kidney tomato cultivation has been one of the main export products within the country, however, its susceptibility to attack by root knot nematodes, especially of the genus (Meloidogyne incognita), has generated a significant decrease in quality, production and commercialization of the crop. This project was carried out in the kidney tomato crop (Solanum lycopersicum L.) located in the parish of La Argelia in the city of Quito, adapted under semi-hydroponic conditions. The main evaluation of these treatments was to determine the efficacy of organic products in the control of nematodes where the effectiveness of an aqueous extract based on castor seeds (Ricinus communis L.), a commercial organic nematicide Nemaquill and an absolute control was evaluated. Starting with a first nematode population analysis before the application of each treatment. The evaluation was carried out in three stages from the application of the treatments, later for the periodic evaluations the population of nematodes was quantified from the extraction and counting protocol described by (Chimba S. & Quimbiulco K., 2020), determining the resulting population after each evaluation. For the management of the experiment, a factorial arrangement (A * B * C) was carried out in DBCA where there were three factors, the factor A corresponding to two nematicides (Commercial Organic Nematicide (A1) and Aqueous Extract of castor (A2); as factor B the population of nematodes present that consisted of two levels, medium population (B1) and high population (B2) considered per 100 g of root and, lastly, factor C that corresponded to the application doses that were three 3,5,7 cc / liter with a total of 13 treatments evaluated, the mean analysis was performed using Tukey significance tests at 5%.